Peningkatan Kinerja karyawan berbasis lingkungan kerja fisik dan keselamatan kerja PT.XYZ di Purwakarta - A.Nurjayadin; Mochamad Vrans Romi (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The physical work environment and work safety continue to be poorly monitored, resulting in a decline in employee performance. Based on data, employee absenteeism continues to increase. A messy and dirty physical work environment makes workers uncomfortable, and work safety remains high. The aim of this research is to find out how the physical work environment and work safety influence the performance of PT.XYZ employees in Purwakarta, both partially and simultaneously. This research uses quantitative methods and primary data, the research population consists of 59 respondents taken using saturated sampling techniques. Data analysis was carried out using multiple regression analysis. Data were processed with SPSS version 26.00